Parameterizing the SFC Baryogenesis Model - Daniela Kirilova; Mariana Panayotova (Advances in Astronomy)
We have numerically explored the scalar field condensate baryogenesis model for numerous sets of model’s parameters, within their natural range of values. We have investigated the evolution of the baryon charge carrying field, the evolution of the baryon charge contained in the scalar field condensate, and the final value of the generated baryon charge on the model’s parameters: the gauge coupling constant α, the Hubble constant at the inflationary stage HI, the mass m, and the self-coupling constants λi.